Role of Local Culture in Recommendation Intentions through Memorable Tourism Experiences - Hidayat, Indra Iryanto Nur; Wisnalmawati, Wisnalmawati; Sugandini, Dyah (Journal of Business Management and Economic Development, 2024)
The main objective of this study is to investigate the effect of local culture on the recommendation intention of tourists who have visited Kebondalem Kidul Cultural Tourism Village, with the mediation of memorable tourism experiences. In this study, a quantitative analysis approach with descriptive analysis was used, using a 5-point Likert scale. The sample collection used a non-probability sampling method, specifically judgment sampling. The sample consisted of 150 respondents who had visited the Kebondalem Kidul Cultural Tourism Village as tourists. Structural Equation Modeling (SEM) SmartPLS 3.2.9 was used as an analytical tool for analysis. Among tourists in Kebondalem Kidul Cultural Tourism Village, local culture directly impacts recommendation intention and memorable tourism experiences. Memorable tourism experiences mediate between local culture and recommendation intention for tourists in the Kebondalem Cultural Tourism Village environment. This research substantially contributes to the existing knowledge regarding local culture in various aspects. The study carries significant practical implications for stakeholders, tourism administrators, and businesses aiming to promote tourism in Kebondalem Kidul Cultural Tourism Village. The findings show that when perceived through memorable tourism experiences, local culture influences tourists' recommendation intention during their trip.